EFEKTIFITAS PEMBELAJARAN PASSING BAWAH PERMAINAN BOLA VOLI MINI DENGAN MENERAPKAN MODIFIKASI BOLA - Tamami Tamami; Abdul Hamid (Lambung Mangkurat University, 2013)
Effectiveness of Learning Games Volleyball Passing Down By Applying Modified Mini Ball. The purpose of this study was aimed to determine the improvement of skills do passing under the mini game volley ball with a modified implementation of the public elementary school students Handil Bakti. The method used in this study is the method of action research (PTK) is in the form of a reflective research. Observations during the learning process takes place and the data analysis is based on observations made by the supervisor. The subjects of this study were fourth grade students at SDN Handil Consecrated Alalak District of Barito Kuala academic year 2013/2014. The number of learners who are the subject of study totaling 41 people. Based on the analysis of data in two cycles, with each cycle of two meetings, that by applying a modified form of a balloon ball and rubber ball showed more effective learning. This situation is expressed by an increase in the average value of each cycle learners. In pre cycle / early observations with an average value of less category (all learners do not pass the study) and then increased in the first cycle at the meeting to 1 still no learners who otherwise completed. Learning continued in the first cycle to the second meeting resulted in 8 or 19.5% pesertadidik thorough. Padasiklus first two meetings to produce 13 or 32% of students who pass the study and the learning cycle to two meetings to 2 experienced significant peningkatn that 41 students (100%) tested thoroughly studied is the excellent category and average learners KKM value already exceeds dditetapkan 70. Keywords: learning effectiveness, pasing down, volleyball, modification